Fabrication and characterization of poly-3-hexylthiophene based organic thin film transistor - Tiwari S.; Balasubramanian S.K.; Tiwari S.; Prakash R. (My University, 2025)
An organic thin film transistor (OTFT) based on chemically synthesized poly-3-hexylthiophene (P3HT) is successfully fabricated and I-V characteristics of the device is measured at room temperature. The key performance parameters such as ON/OFF ratio, threshold voltage, carrier mobility, conductivity and transconductance are extracted through the I-V characteristics of OTFT and discussed in the paper. © 2012 IEEE.